Cross-layer resource scheduling scheme in WiMAX mesh networks - Jiao, Yi (2013)
Due to the complicated architecture of the mesh mode in WiMAX networks, resource scheduling is a significant but difficult problem. Appropriate resource scheduling scheme is capable of improving the network capacity. This work, based on an odd-even layered architecture, proposes a cross-layer resource scheduling scheme. The proposed scheme operates at medium access control (MAC) layer and physical (PHY) layer. At MAC layer, a hierarchical bandwidth allocation algorithm is designed to enhance concurrent transmissions and thus the network throughput. At PHY layer, a power control algorithm is derived to reduce interferences and meet the demands of links at different layers. Experimental results validate the availability and effectiveness in terms of resource utilization and network throughput.